2021
DOI: 10.1152/ajpcell.00379.2020
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue inflammation and metabolic dysfunction in obesity

Abstract: Several lines of preclinical and clinical research have confirmed that chronic low-grade inflammation of adipose tissue is mechanistically linked to metabolic disease and organ tissue complications in the overweight and obese organism. Despite this widely confirmed paradigm, numerous open questions and knowledge gaps remain to be investigated. This is mainly due to the intricately intertwined crosstalk of various pro- and anti- inflammatory signaling cascades involved in the immune response of expanding adipos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
414
3
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 762 publications
(607 citation statements)
references
References 244 publications
7
414
3
13
Order By: Relevance
“…Both physical stress and chronic inflammation could be underlying the association between high BMI and height loss. High BMI is known to be associated with chronic inflammation [ 30 ]. A previous study reported that inflammation may play an important role in the etiology of fractures in men [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both physical stress and chronic inflammation could be underlying the association between high BMI and height loss. High BMI is known to be associated with chronic inflammation [ 30 ]. A previous study reported that inflammation may play an important role in the etiology of fractures in men [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the participation of the immune system and the development of low-grade chronic inflammatory syndrome with this pathology has been evidenced. The role of systemic inflammation with obesity, especially with its abdominal type, is aslo demonstrated [ 13 , 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…Uncontrolled accumulation of adipose tissue occurring in obesity leads to the onset of a whole series of metabolic syndrome and pathological conditions [9]. In addition, the establishment of a state of chronic low-grade inflammation induces the infiltration of bone marrow-derived immune cells, negatively impacting organ function [41]. Our results showed a reduced number of mature adipocytes when ADSCs were cultured in the presence of vitamin D, or metformin, or both (Figure 1), despite the presence of the adipogenic conditioned media, as compared to cells exposed to MD alone, showing the typical morphology of mature adipocytes.…”
Section: Discussionmentioning
confidence: 99%